Interdisciplining Digital Humanities : Boundary Work in an Emerging Field - Klein, Julie Thompson (Book collections on Project MUSE., 2015)
Interdisciplining Digital Humanities sorts through definitions and patterns of practice over roughly sixty-five years of work, providing an overview for specialists and a general audience alike. It is the only book that tests the widespread claim that Digital Humanities is interdisciplinary. By examining the boundary work of constructing, expanding, and sustaining a new field, it depicts both the ways this new field is being situated within individual domains and dynamic cross-fertilizations that are fostering new relationships across academic boundaries. It also accounts for digital reinvigorations of public humanities in cultural heritage institutions of museums, archives, libraries, and community forums.--